Respuesta :

Answer:

i

Step-by-step explanation:

note that [tex]\sqrt{-1}[/tex] = i

Given

[tex]\sqrt{-25}[/tex] - [tex]\sqrt{-16}[/tex]

= [tex]\sqrt{25(-1)}[/tex] - [tex]\sqrt{16(-1)}[/tex]

= [tex]\sqrt{25}[/tex] × [tex]\sqrt{-1}[/tex] - ( [tex]\sqrt{16}[/tex] × [tex]\sqrt{-1}[/tex])

= 5i - 4i

= i

Answer:  c) i

Step-by-step explanation:

[tex]\sqrt{-25}-\sqrt{-16}\\\\=\sqrt{-1\cdot 5\cdot 5}-\sqrt{-1\cdot 4\cdot 4}\\\\=5i-4i\qquad \qquad \qquad \qquad \text{Note: }\sqrt{-1}=i\\\\=i[/tex]